2022
DOI: 10.3390/plants11111522
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation and Genotype by Environment Interaction for Agronomic Traits in Maize (Zea mays L.) Hybrids

Abstract: In order to develop high-yielding genotypes of adapted maize, multilocation trials of maize were performed including forty-five maize hybrids exploiting genetic variability, trait associations, and diversity. The experiments were laid out in an RCB design and data were recorded on eight yield and yield-contributing traits, viz., days to anthesis (AD), days to silking (SD), anthesis–silking interval (ASI), plant height (PH), ear height (EH), kernels per ear (KPE), thousand-kernel weight (TKW), and grain yield (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Consistently, the genotypic coefficient of variation (GCV) percentages of DM, PH, PL and TW traits were also higher than their corresponding environmental coefficient of variation (ECV) percentage (Table 2). Broad-sense heritability (H 2 ) captures the proportion of σ 2 p due to genetic effects and is expressed as the ratio of σ 2 g to σ 2 p [19]. In this study, H 2 exhibited a range of 65.37 to 96.31% in DM, PH, TW and PL traits (Table 2), indicating a substantial genetic influence contributing to the observed diversity within the Aus rice pop-ulation.…”
Section: Effects Of Genetic and Environmental Components On The Agron...mentioning
confidence: 74%
“…Consistently, the genotypic coefficient of variation (GCV) percentages of DM, PH, PL and TW traits were also higher than their corresponding environmental coefficient of variation (ECV) percentage (Table 2). Broad-sense heritability (H 2 ) captures the proportion of σ 2 p due to genetic effects and is expressed as the ratio of σ 2 g to σ 2 p [19]. In this study, H 2 exhibited a range of 65.37 to 96.31% in DM, PH, TW and PL traits (Table 2), indicating a substantial genetic influence contributing to the observed diversity within the Aus rice pop-ulation.…”
Section: Effects Of Genetic and Environmental Components On The Agron...mentioning
confidence: 74%
“…High phenotypic and genotypic coefficients of variation for PHT and main panicle yield, moderate for panicle length, and low for the flowering date have also been reported [17,41]. The small difference between genotypic and phenotypic coefficients of variation for most traits, with the exception of SDI, may indicate a very low environmental influence on these traits [42] and a higher genetic control of their expression. The high heritability of these traits confirms the weak influence of environmental factors on their expression.…”
Section: Discussionmentioning
confidence: 95%
“…Genotypes collected from the same source didn't always fall into the same group, again differentially derived ones were included in the same group. It's indicated that the geographical distribution of the genotypes doesn't confirm the homogeneity [58,73]. Divergent groups were formed based on genotype performances in earlier studies [58,74].…”
Section: Plos Onementioning
confidence: 98%